ÁCIDO 2-CLOROETILFOSFÔNICO NO RALEIO DE AMEIXEIRAS EM PÓS FLORADA - Pavanello, Alexandre Pozzobom (2012)
Fruit thinning is one of the main practice to produce good quality fruit today. It promotes a balance between vegetative growth and production, increases fruit size and avoids alternation of production. Thinning can be done during flowering, but its often done later after fruit set, which can be defined best fruiting. Manual thinning of large number of plants is not practical or economical. An alternative is chemical thinning, which involves the application of chemicals on flowering or right after flowering and leads to fruit abscission, reducing or eliminating manual thinning. The objectives of this trial was to evaluate the effect of different concentrations of ethephon (2-chloroethylphosphonic) in chemical thinning of plum cvs. Irati, Reubennel during the harvest of 2010/2011 and 2011/2012 and its economic feasibility in Arapoti-PR. East central region of Paraná. The following characteristics were evaluated, number of fruits per branch, per plant, production, medium weight, firmness, soluble solids, pH, acidity and color. In the season 2010/2011, it was observed that increased concentration of ethephon linearly decreased the number of fruit caliber I, II, III, since the gauge IV had a higher number of fruits on the estimated concentration of 0.093 mL L ethephon and necessary to drive studies at lower concentrations, which were made in 2011/2012 harvest. In this harvest, the estimated concentration of 0.07 mL L ethephon, cv. Irati produced 23 kg/plant and the cv. Reubennel 73 kg/plant having satisfactory quantity of fruit size III and IV. The use of ethephon decreased the firmness of the fruits for cv. Irati and did not influenced the cv. Reubennel. None of the concentrations of ethephon affected the physical and chemical quality of fruits in relation to total soluble solids, pH and acidity for both crops and cvs. Economical evaluation of both cvs., showed that productivity and net income of treatment with etehephon gave better results than other treatments. Manual thinning showed a higher percentage gave better results than other treatments. Manual thinning showed a higher percentage of fruit size III and IV but at higher cost, which is difficult to sustain in time, due to high cost and availability of skilled labor force in the region, which indicates that chemical thinning will be a good economical alternative.